Balloon-borne tropospheric CO2 observations over the equatorial eastern and western Pacific. (July 2018) - Inai, Yoichi; Aoki, Shuji; Honda, Hideyuki; Furutani, Hiroshi; Matsumi, Yutaka; Ouchi, Mai; Sugawara, Satoshi; Hasebe, Fumio; Uematsu, Mitsuo; Fujiwara, Masatomo
Abstract: Vertical profiles of carbon dioxide (CO2 ) mixing ratio in the equatorial eastern and western Pacific were measured by newly developed balloon-borne CO2 sondes in February 2012 (two soundings) and February–March 2015 (four soundings), respectively. The 1–10 km vertically averaged CO2 mixing ratios lie between the background surface values in the Northern Hemisphere (NH) and those in the Southern Hemisphere (SH) monitored at ground-based sites during these periods. A backward trajectory analysis, taking account of convective mixing processes using geostationary satellite cloud-image data, is applied to the measured CO2 profiles to estimate the origin of the observed air masses. Air masses originating in the SH show low CO2 mixing ratios that are similar to the background values in the SH. This relationship is confirmed by a positive correlation (∼0.6) between the CO2 mixing ratio and the latitude of air mass origin which is found from trajectory calculations. This result suggests that the CO2 distribution in the troposphere over the equatorial Pacific is controlled by monthly time-scale, large-scale CO2 distribution and weekly time-scale atmospheric transport processes. Furthermore, this study shows that the combination of CO2 sonde measurements and trajectory analysis, taking account of convective mixing, is a useful tool in investigating CO2 transport processes. Highlights: CO2 sondes flown in the equatorial Pacific where few CO2 profile have been reported. Trajectory analysis was performed by taking convective mixing into account. Observed CO2 was interpreted by the backgrounds and long-range transport.